2009
DOI: 10.1073/pnas.0906465106
|View full text |Cite
|
Sign up to set email alerts
|

The actin-like MreB cytoskeleton organizes viral DNA replication in bacteria

Abstract: Little is known about the organization or proteins involved in membrane-associated replication of prokaryotic genomes. Here we show that the actin-like MreB cytoskeleton of the distantly related bacteria Escherichia coli and Bacillus subtilis is required for efficient viral DNA replication. Detailed analyses of B. subtilis phage 29 showed that the MreB cytoskeleton plays a crucial role in organizing phage DNA replication at the membrane. Thus, phage double-stranded DNA and components of the 29 replication mach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 43 publications
1
54
0
Order By: Relevance
“…S3B). ϕ29 TP Recruits the Phage DNA Polymerase to the Bacterial Nucleoid, and Both Proteins Subsequently Are Redistributed in a Helix-Like Manner. We previously showed that ϕ29 DNA polymerase localizes uniformly in non-infected cells, and that at middle stages of the infection cycle, it localizes into clear helix-like structures in B. subtilis (11). Nevertheless, at 10 min postinfection, the ϕ29 DNA polymerase fused to YFP (YFP-p2) colocalizes with the bacterial nucleoid (Fig.…”
Section: N-terminal Domain Of the Tp Is Responsible For Its Nucleoidmentioning
confidence: 99%
See 2 more Smart Citations
“…S3B). ϕ29 TP Recruits the Phage DNA Polymerase to the Bacterial Nucleoid, and Both Proteins Subsequently Are Redistributed in a Helix-Like Manner. We previously showed that ϕ29 DNA polymerase localizes uniformly in non-infected cells, and that at middle stages of the infection cycle, it localizes into clear helix-like structures in B. subtilis (11). Nevertheless, at 10 min postinfection, the ϕ29 DNA polymerase fused to YFP (YFP-p2) colocalizes with the bacterial nucleoid (Fig.…”
Section: N-terminal Domain Of the Tp Is Responsible For Its Nucleoidmentioning
confidence: 99%
“…We previously demonstrated that the helical localization of the ϕ29 DNA polymerase at middle stages of infection is lost in mreB cytoskeleton mutant strains (11). To investigate whether the helical-like redistribution of ϕ29 TP also depends on MreB, we examined the subcellular localization of YFP-TP in an mreB deletion mutant.…”
Section: N-terminal Domain Of the Tp Is Responsible For Its Nucleoidmentioning
confidence: 99%
See 1 more Smart Citation
“…They are responsible for proper chromosome segregation and movement, as well as for cell-wall integrity during elongation and division (22,(26)(27)(28)(29). Interestingly, two proteins of Bacillus Φ29 phage interact with FtsZ and MreB, but in contrast to the T7 proteins, they do not inhibit them but rather exploit them for phage replication (30). The fact that FtsZ has been shown to confer a competitive advantage to the phage merely via inhibition of FtsZ suggests that this is also the case for MreB.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between actin and hnRNPs, which bridges transcription, chromatin remodeling and pre-mRNA processing, is an excellent example of how actin acts to bring different macromolecular assemblies together [Sjolinder et al, 2005;Obrdlik et al, 2008]. A prokaryotic example of this could be MreB, which organizes bacteriophage replication by anchoring the viral DNA to membrane proteins [Munoz-Espin et al, 2009]. As actin has a limited surface area, the competition between different factors for binding to actin may therefore act to regulate different nuclear and prokaryotic processes.…”
Section: Conclusion and Further Perspectivesmentioning
confidence: 99%